Os verbos de movimento no português brasileiro - Leticia Lucinda Meirelles (2016)
In this dissertation, we analyze motion verbs in Brazilian Portuguese. These verbs describe situations in which an entity performs some motion, voluntarily or involuntarily, (TALMY, 1985, 2000), with or without a path. Our aim is to describe the semantic and syntactic properties of these verbs in order to group them in verbal classes and represent their semantic structure by means of the predicates decomposition metalanguage. We assume, based on works at the Interface Syntax-Lexical Semantics, that verbs which have the same syntactic behavior must have semantic properties in common (LEVIN, 1993; PINKER, 1989; LEVIN; RAPPAPORT HOVAV, 2005; CANÇADO; GODOY; AMARAL, 2013a). We base our work on proposals by Levin and Rappaport Hovav (1992), Levin (1993) and Jackendoff (1990), who argues that English motion verbs do not constitute a single class. We checked whether the same is true for Brazilian Portuguese and we reached the conclusion that in that language motion verbs are divided into five different classes. Therefore, we conclude that the semantic property motion is not relevant to the division of the Brazilian Portuguese verbs into classes that determine their syntactic behavior and that the semantic representation of this property is not made, mostly, through specific motion primitives. This occurs because this semantic property is part of the idiosyncratic meaning of some verbs or is derived from the verbs lexical representation.